A Quantitative Pilot Study on Donation after Cardiac Death (DCD): Perceptions felt by the Nursing and Medical Staff in Intensive Care Units (ICU) of Geneva University Hospitals and Lausanne University Hospital. (August 2017) - Zellweger, Alessia; Eckert, Philippe; Karam, Oliver; Cedraschi, Christine; Moretti, Diane; Majmou, Hasna; Carre, Delphine; Ludwig, Virginie; Gasche, Yvan
Abstract : Aim: DCD is considered a viable solution to reduce organ shortage, but it raises serious ethical and psychological issues that cannot be ignored. Understanding what alters DCD acceptance by ICU caregivers is important to run a sustainable DCD program and to offer an adapted support for the personnel involved. The aim of our research was to shed new light on feelings experienced by caregivers regarding DCD. Methods: We developed a questionnaire which aims to identify caregivers' opinions concerning DCD. Our survey incorporates a list of questions to examine ethical issues regarding therapy withdrawal and organ donation. The sample includes ICU caregivers (physicians, nurses and care assistants) at the Geneva and Lausanne University Hospitals. Data were collected using LogiIC software and Survey Monkey and then analysed through Statistical Package for Social Sciences -SPSS V.22.0. In both hospitals, our research was conducted before the introduction of the DCD program. Results: 106 ICU professionals responded, 66% nurses, 30% physicians and 4% care assistant. Analysis shows that the most crucial ethical issues concentrated around four main topics. 1) Presence of some doubts concerning the real reasons leading to withdrawal of life support: 42% of respondent think that withdrawal of life support decision was not always taken in the interest of the patient; 2) Satisfactory level of support within ICU during end-of-life care: 49% of ICU nurses feel being reasonably well supported and 47% feel rather well or very well supported; 3) Hastening of patient death because of palliative treatments isn't a main source of concern: in Geneva respondents perceive that this acceleration rather gives them a sense of relieve (52%). Lausanne data also show that 80% of respondent claim that they do not feel any conflict of interest in this context; 4) Independence between the therapeutic withdrawal and the decision to donate is reasonably well preserved: 73% of caregivers do not feel any conflict of interest during DCD procedure. Finally, our survey demonstrate that ICU professional were in favour of organ donation not only in DBD context (97%) but also in DCD (94%). In addition, 70% of caregivers' trust in DCD program development. Conclusions: The introduction of DCD in the ICU, challenges the ethical values of caregivers. Nevertheless, our findings suggest that caregivers generally embrace DCD as a valid practice for patients who do not fulfil brain death criteria. A pilot study on DCD perceptions felt by the nursing and medical staff in adult intensive care unit (ICU) of Geneva University Hospitals and Lausanne University Hospital. This study was financially supported by the Department of Anaesthesiology, Pharmacology and Intensive Care Medicine Research Fund. The Geneva University Hospital DCD program is financially supported by the Geneva University Hospitals Private Foundation. We also gratefully acknowledge the support of Dr. Didier Tassaux, MD, PhD; Josette Simon and also all the ICU personnel who has always been highly collaborative .